The Sunset of Anthropocentric Ontology: Post-Biological Man - Nahapetyan, Ovsanna (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
As a result of the disproportionate development of human creative abilities and the spiritual and moral progress of humanity, the moral context of modern human life has begun to wear out and shrink like “shag leather”. The problem is that the science and the latest technological achievements of the era of postmodernity have not only fundamentally changed ( and are changing) the objective foundations of the once ontological order of human life, but also the essence and nature of the human being, both in his body and moral perceptions, and spiritual inner world in general. This new type of man is no longer a bodily singularity, since this mixture of biological and technical organs (cyborg), modified at the genetic level and representing the superman of our time, no longer expresses the essence of the natural man (the self) and is transformed into a technically replaceable formation. Moreover, in our consumer world that is aimed at satisfying insatiable material needs, men, henceforth, are valued from the perspective of “efficiency” in contributing to economic prosperity. This is an undeniably worrying reality, which requires a new understanding of the process and consequences of the transformations of the constants (sociality, morality, the meaning of life, perfection, humanity) that embody the structure of the spiritual context of human social ontology.